2009
DOI: 10.4085/1062-6050-44.5.531
|View full text |Cite
|
Sign up to set email alerts
|

Topical Silver for Infected Wounds

Abstract: Reference/Citation: Vermeulen H, van Hattem JM, Storm-Versloot MN, Ubbink DT. Topical silver for treating infected wounds. Cochrane Database Syst Rev. 2007(1);CD005486. Clinical Question: What is the clinical evidence base for silver dressings in the management of contaminated and infected acute and chronic wounds? Data Sources: Investigations were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 4 publications
0
30
1
1
Order By: Relevance
“…[21] On the other hand, the beneficial effects of silver on wound biology due to its potent antimicrobial activity have been overlooked in general until recently. However, compilations which address studies related to silver therapeutics and silver-release dressings treatment state that [22,23] there is "no clear evidence to support the use of silver-containing foam and alginate dressings in the management of infected wounds" [22] and "it is clear also that the effects of the various silver products available on wound infection and wound healing are variable. Understanding the characteristics of these products and dressings may enable them to be targeted more appropriately according to the specific requirements".…”
Section: Kıyan Et Al Investigation Of Acute Effects Of Hypericum Permentioning
confidence: 99%
“…[21] On the other hand, the beneficial effects of silver on wound biology due to its potent antimicrobial activity have been overlooked in general until recently. However, compilations which address studies related to silver therapeutics and silver-release dressings treatment state that [22,23] there is "no clear evidence to support the use of silver-containing foam and alginate dressings in the management of infected wounds" [22] and "it is clear also that the effects of the various silver products available on wound infection and wound healing are variable. Understanding the characteristics of these products and dressings may enable them to be targeted more appropriately according to the specific requirements".…”
Section: Kıyan Et Al Investigation Of Acute Effects Of Hypericum Permentioning
confidence: 99%
“…Although chemicals may facilitate debridement, their use is controversial and not recommended for acute skin trauma. 71,73,74 Some authors have recommended chemicals for debridement of infected wounds 71 or with wet-to-moist debridement. 75 The effervescent effect of hydrogen peroxide may aid debridement, but hydrogen peroxide and sodium hypochlorite are thought to be cytotoxic to healthy granulation tissue.…”
Section: 70mentioning
confidence: 99%
“…For SNC, 3.4% of patients concluded their participation in 0-7 days, 34.4% in 8-14 days, 37.9% in 15-21 days, and 24.1% in ≥21 days. The distribution of economic costs in the SSD group was as follows: 42.9%, 57.2%, while in the SNC group, the distribution was as follows: 48.2%; 48.3%;3.4%. Conclusion: There is no statistical significance in the results of this study; however, in percentage, SNC are superior regarding the rate of wound granulation, antibiotic effect, and healing time.…”
mentioning
confidence: 99%
“…In fact, there have been some studies that have shown benefits on the use of these silver-based compounds over other preparations such as iodine not only with respect to wound granulation but also regarding their antibiotic effects against some specific microorganisms such as Staphylococcus aureus, Streptococcus pneumoniae, and Pseudomonas aeruginosa, with a very low rate of side effects. [3][4][5][6][7][8] However, other studies have questioned these results, after comparing the effectiveness of silver-based compounds with other commonly used drugs. 9,10 The purpose of this investigation was to determine the most frequent soft tissue lesions and to compare the effectiveness of nanocrystals and SSD with regard to the rate of granulation of wounds, the antibiotic effect, the duration of treatment, and the economic cost.…”
mentioning
confidence: 99%